2006
DOI: 10.1111/j.1365-2125.2006.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation associated with sibutramine treatment

Abstract: Aims To investigate a possible association of sibutramine with QT interval prolongation. Methods Post‐marketing surveillance using prescription event monitoring in the New Zealand Intensive Medicines Monitoring Programme (IMMP) identified a case of QT prolongation and associated cardiac arrest in a patient taking sibutramine for 25 days. This patient was further investigated, including genotyping for long QT syndrome. Other IMMP case reports suggesting arrhythmias associated with sibutramine were assessed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…A total of 6.3% of patients became tachycardic, and mean pulse rate increased by 2.5 bpm. No patients developed arrhythmias, but there are reports of ventricular ectopy and prolonged QT syndrome in a few patients treated with sibutramine (47). Sibutramine can also cause insomnia (3.2% of adolescents), dizziness (4%), dry mouth, and constipation and must not be used with monoamine oxidase inhibitors or a variety of other medications that can cause the serotonin syndrome (24).…”
Section: Study Attrition Rates and Adverse Effects Of Pharmacologic Amentioning
confidence: 99%
“…A total of 6.3% of patients became tachycardic, and mean pulse rate increased by 2.5 bpm. No patients developed arrhythmias, but there are reports of ventricular ectopy and prolonged QT syndrome in a few patients treated with sibutramine (47). Sibutramine can also cause insomnia (3.2% of adolescents), dizziness (4%), dry mouth, and constipation and must not be used with monoamine oxidase inhibitors or a variety of other medications that can cause the serotonin syndrome (24).…”
Section: Study Attrition Rates and Adverse Effects Of Pharmacologic Amentioning
confidence: 99%
“…Further studies are required, but sibutramine should be avoided in patients with long QT syndrome and in patients taking other medicines that may prolong the QT interval. [89] Another paper reported on a probable association between sibutramine and QT interval prolongation leading to ventricular fibrillation and cardiac arrest in a 51-year-old woman with obesity but no other relevant past medical history or cardiac risk factors. [90] In vitro studies demonstrated that sibutramine preferentially inhibits the hERG potassium channel, in a concentration-dependent manner, an effect that may contribute to prolong the cardiac action potential duration associated with long QT syndrome.…”
Section: -Recent Case Reports Of Arrhythmia or Acute Myocardial Infarmentioning
confidence: 99%
“…There are two previously published reports of sibutramine‐induced cardiac arrest, but in both cases, sibutramine was prescribed for 1–4 months to treat obesity before the cardiac arrest 4, 5. In the reported cases4, 5 and also the present patient, the QT interval was significantly prolonged at admission and was normalized after discontinuation of sibutramine. The significant impact of this agent on ventricular repolarization, that is, significant increase in QT dispersion, was shown in 65 consecutive patients 6.…”
Section: Discussionmentioning
confidence: 52%